2023
DOI: 10.1039/d3cc02130k
|View full text |Cite
|
Sign up to set email alerts
|

Variable temperature kinetic isotope effects demonstrate extensive tunnelling in the C–H activation reactivity of a transition metal-oxo complex

Abstract: There has been recent interest about how the rates of concerted proton electron transfer (CPET) are affected by the thermodynamic parameters of intermediates from stepwise PT or ET reactions. Semiclassical...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 43 publications
4
9
0
Order By: Relevance
“…The relative rate constants from these calculations give a satisfyingly good agreement with experimental kinetic trends with p K a (Figure A) and kinetic isotope effects (KIEs) (Figure B). , This good correspondence validates our analysis presented above of how the proton energy wells affect the reactivity of CoO . Furthermore, it suggests that changes in energy well curvature may be the source of stepwise thermodynamic effects in C–H activations more generally.…”
supporting
confidence: 92%
See 2 more Smart Citations
“…The relative rate constants from these calculations give a satisfyingly good agreement with experimental kinetic trends with p K a (Figure A) and kinetic isotope effects (KIEs) (Figure B). , This good correspondence validates our analysis presented above of how the proton energy wells affect the reactivity of CoO . Furthermore, it suggests that changes in energy well curvature may be the source of stepwise thermodynamic effects in C–H activations more generally.…”
supporting
confidence: 92%
“…We recently reported experimental evidence for extensive tunneling in the Co–oxo complex PhB­( t BuIm) 3 Co III O ( CoO ) for which the rate of concerted C–H activation trends with Δ G ° PT instead of Δ G ° CPET (Scheme ). , To better understand these seemingly semiclassical reactivity trends in a system with established extensive tunneling, we computationally examined the reactivity of CoO with C–H bonds. Our calculations demonstrate that the experimentally observed reactivity trend stems from a lower Δ G ° PT leading to a more anharmonic energy well for the reactant.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Following Shaik's approach, we attribute this observation to its higher basicity (ΔpK a > 17), resulting in a narrower barrier with increased QMT probability. Importantly, our results complement those of Anderson for a basic cobalt(III) oxo complex (A) with significant deviations from BEP behavior, [9,14] but also those for Tolman's distinctly basic copper(III) hydroxo complexes. [15] The growing number of examples thus suggests that thermochemical data might be useful predictors for CÀ H activation selectivities under QMT control.…”
Section: Zuschriftensupporting
confidence: 80%
“…[13] However, detailed CÀ H/D kinetic isotope effect (KIE) studies for A also indicated significant variation in Htunneling contributions with different substrates. [14] Similar observations were reported for Tolman's distinctly basic copper(III) hydroxo complexes. [15] Shaik and co-workers ascribed deviations from BEP characteristics of a series of Fe IV O complexes to quantum-mechanical tunneling (QMT).…”
supporting
confidence: 72%